Navigating digital inclusion and the digital vā among Niue mamatua through the provision of mobile phones during COVID-19. (March 2023) - Matenga-Ikihele (Te Whānau-ā-ApanuiNiue), Amio; Fa'alau, Fuafiva; Dobson, Rosie; Fa'alili-Fidow, Jacinta; Roberts, Mary; Taufa, Seini; Tuesday, Ruby; Whitakker, Robyn; McCool, Judith
Technology and digital platforms have become essential for people and communities to interact because of COVID-19. Despite its benefits, digital exclusion disproportionately affects Pacific communities living in New Zealand. This article provides insights into how Niue mamatua (older adults) used their gifted mobile phones and mobile data as part of a COVID-19 digital inclusion initiative. It begins with an overview of the digital inclusion needs of older adults, followed by a description of the digital vā (relational space) and negotiating a new way of maintaining connection in an online world. The tutala (a Niue method of conversation anchored on respect) with 12 mamatua highlighted the benefits, support factors, and challenges of how they were able to use their mobile phone. Importantly, mobile phones provided the necessary access and connectivity to interact in a digitally connected world, namely the digital vā, when in-person connections were disrupted because of COVID-19.